2007
DOI: 10.1002/elan.200603775
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Nanostructured Membranes (ENM): Synthesis and Electrochemical Properties of Redox Mediator‐Modified Gold Nanoparticles Using a Dendrimer Layer‐by‐Layer Approach

Abstract: The layer-by-layer (LbL) self-assembly process has become an important tool in the fabrication of nanostructured devices for electrochemical applications, especially in those cases where control at the molecular level is required. In this paper we present a system based on electroactive nanostructured membranes (ENM) with ITO-PVS/PAMAM-Au LbL electrodes, in which a redox mediator (Me) is electrodeposited around the Au nanoparticles to form an ITO-PVS/ PAMAM-Au@Me system. The redox mediators used were Co, Fe, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
7

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
1
19
0
7
Order By: Relevance
“…Assuming that the ferrocenyl guests immobilized on the smallest size dendrimers might be confined more closely than those borne on the larger dendrimers, it could be expected that the largest adsorbateadsorbate repulsive interactions should be observed for the former situation and decrease gradually as an inverse function of the dendritic generation. [29][30][31][32][33] Table 2 gives the values of K, G t=0 ads , and a that were obtained by fitting the Frumkin-isotherm curves to the data in Figure 4. As it can be seen from the fitted values, the association constant K for adsorption onto the immobilized Fc varied inversely with the dendritic size, and G t=0 ads became more negative.…”
Section: Binding Of CD With Fc Tethered To the Dendrimer Filmsmentioning
confidence: 99%
“…Assuming that the ferrocenyl guests immobilized on the smallest size dendrimers might be confined more closely than those borne on the larger dendrimers, it could be expected that the largest adsorbateadsorbate repulsive interactions should be observed for the former situation and decrease gradually as an inverse function of the dendritic generation. [29][30][31][32][33] Table 2 gives the values of K, G t=0 ads , and a that were obtained by fitting the Frumkin-isotherm curves to the data in Figure 4. As it can be seen from the fitted values, the association constant K for adsorption onto the immobilized Fc varied inversely with the dendritic size, and G t=0 ads became more negative.…”
Section: Binding Of CD With Fc Tethered To the Dendrimer Filmsmentioning
confidence: 99%
“…In previous work, three bilayers of PVS/PAMAM-Au was found to be the best configuration to prepare an ITO modified electrode, since 3-bilayer PVS/PAMAM-Au LbL films were found to possess high organisation and outstanding uniformity [8].…”
Section: Preparation Of An Electroactive Nanostructured Membrane (Enmmentioning
confidence: 99%
“…We previously showed that ITO-(PVS/PAMAM-Au) 3 structures are suitable for biosensors and electrocatalysis owing to their low capacitive and high Faradaic currents associated with low ohmic drop [8]. Electrodeposition by potential cycling of cobalt hexacyanoferrate onto ITO-(PVS/PAMAM-Au) 3 electrodes was carried out according to the optimised conditions in previous work [7,16].…”
Section: Preparation Of An Electroactive Nanostructured Membrane (Enmmentioning
confidence: 99%
See 2 more Smart Citations